Language and Music : Based on Tsova-tush (Batsbi) Folklore Materials - Shavkhelishvili, Bela; Vamling, Karina (Actual Problems of Kartvelology, 2025)
The topic of “language and music” itself is a relatively new topic in terms of study, and Tsova-Tushuri has never been the subject of serious linguistic scientific observation, despite the fact that musical folklore has long been studied by Georgian musicologists, folklorists and historians. The identity of the Tsova-Tush is very clearly expressed in their musical folklore and is part of the unified melodies of the mountaineers of Eastern Georgia. People can borrow lexical units in the language, some component of clothing, a recipe for foreign cuisine, but it is very difficult to imagine that a whole group would sing to a foreign motif... Thus, we can only confirm the fact that the culture of the Tsova-Tushuri is identical to the Georgian self-consciousness. Let us think together about the path we have taken to preserve languages, dialects, and dialects as treasures that our ancestors have carefully preserved for our generation.